Postmodern Aristotles: Arendt, Strauss, and MacIntyre, and the recovery of political philosophy - Pinkoski, N (2017)
What is political philosophy? Aristotle pursues that question by asking what the good is. If Nietzsche's postmodern diagnosis that modern philosophical rationalism has exhausted itself is true, it is unclear if an answer to that question is possible. Yet given the prevalence of extremist ideologies in 20th century politics, and the politically irresponsible support of philosophers for these ideologies, there is an urgent need for an answer. This thesis examines how, in these philosophical circumstances, Hannah Arendt, Leo Strauss, and Alasdair MacIntyre conclude that a key resource in the recovery of political philosophy, and in showing its contemporary relevance, lies in the recovery of Aristotle's political philosophy. This thesis contends that how and why Arendt, Strauss, and MacIntyre turn to Aristotle, and what they find in Aristotle, depends on their varying critiques of modernity. Convinced that the philosophical tradition is shattered irreversibly after the events of totalitarianism, Arendt argues for a retrieval of Aristotle and his understanding of politics from the fragments of that tradition. Strauss is impelled to turn to the political philosophy of Aristotle because of the crisis of radical historicism, to recover classical rationalism’s answer to what the good is. MacIntyre turns to Aristotle to find the moral justification for rejecting Stalinism that contemporary philosophical traditions fail to provide; he reconstructs an Aristotelian tradition that can answer the question of what the good is better than his contemporary rivals. Although these thinkers may appear disparate, this thesis argues that each addresses the question of what the good is by offering a vision of political philosophy as a way of life, which Aristotle helps form. This way of life probes the relationship between philosophy and politics as permanent problem for human existence. In recovering this tradition of thinking with Aristotle about the character of political philosophy, this thesis aims to contribute to the understanding of each of these thinkers, as well as to the practice of political philosophy in modern, post-Nietzschean times.